Tarpukario Lietuvoje matematikos studijoms skiriamų mokomųjų valandų lyginamoji analizė - Ragalytė, Birutė; Paukštienė, Alma (Lietuvos matematikos rinkinys, 2021)
Analysis of time which is designated for mathematics studies in Lithuania between two world wars is presented in this article. The history of education is described. Comparisions between European countries (France, Austria, Germany) and Lithuania of this period are presented in this article.